Journal of Greek Archaeology Volume 4: Editorial - Bintliff, John (Journal of Greek Archaeology, 2019)
This our fourth volume is unusually rich and varied in content. Geographically the articles range from Sicily via Greece to Anatolia and the Near East, while chronologically they extend from the Bronze Age to the Ottoman era. Thematically we have a set of papers in landscape studies which include agricultural history, settlement geography, regional comparisons; articles on material culture which encompass metallurgy, ceramics, the links between language and artefacts, and production and trade; papers on aspects of human social science such as palaeopathology and deformity, gender studies and the representation of the supernatural; historical perspectives are finally represented by articles on fortifications and Islamisation. A special treat is a lengthy presentation of the survey and excavation at the recently-discovered Mycenaean palace in the Sparta Valley. Our review section is even broader, running from the Palaeolithic through to aspects of presentday heritage studies, and covering an equally wide field of topics.